Dynamically reconfigurable fibre optical spanner - Kolb, Thorsten; Albert, Sahradha; Haug, Michael; Whyte, Graeme (Lab on A Chip, 2014)
In this paper we describe a pneumatically actuated fibre-optic spanner integrated into a microfluidic Lab-on-a-Chip device for the controlled trapping and rotation of living cells. The dynamic nature of the system allows interactive control over the rotation speed with the same optical power. The use of a multi-layer device makes it possible to rotate a cell both in the imaging plane and also in a perpendicular plane allowing tomographic imaging of the trapped living cell. The integrated device allows easy operation and by combining it with high-resolution confocal microscopy we show for the first time that the pattern of rotation can give information regarding the sub-cellular composition of a rotated cell.
EAM Import::2019-03-13